IDENTIFICATION OF ANTIOXIDANT COMPOUNDS IN BOERHAAVIA DIFFUSA MOTHER TINCTURE THROUGH MASS SPECTROMETRIC ANALYSIS (CAHIERS MAGELLANES-NS, 2024)
Boerhaavia diffusa is a medicinal plant extensively utilised in traditional medicine for its antioxidant and therapeutic properties. This work seeks to discover and analyse the antioxidant components in Boerhaavia diffusa mother tincture using mass spectrometric analysis. The antioxidant capacity of these compounds was subsequently assessed by in vitro experiments to validate their effectiveness. The research utilised mass spectrometry (MS) to identify bioactive chemicals. The mass spectrometric study discovered roughly 6000 molecules, with 99 important ones noted for their considerable antioxidant capabilities. The compounds were classified according to their mass-to-charge ratios (m/z) and molecular weights. Prominent components were ascorbic acid, alpha-tocopherol, beta-carotene, curcumin, and chlorogenic acid, each recognised for their significant antioxidant properties. The existence of flavonoids, carotenoids, and phenolic acids reinforces the medicinal function of Boerhaavia diffusa in alleviating oxidative stress. The variety of antioxidant components indicates a synergistic effect, enhancing the total therapeutic efficacy of the mother tincture. This study concludes that Boerhaavia diffusa mother tincture is a substantial source of bioactive antioxidant chemicals, with potential uses in the prevention and control of oxidative stress-related disorders. Further research is necessary to investigate its therapeutic qualities across various potencies and formulations for expanded medicinal uses.